Differentiated Thyroid Cancer Outcomes After Surgery and Activity-Adjusted 131I Theragnostics. (January 2019) - Avram, Anca M.; Rosculet, Natalja; Esfandiari, Nazanene H.; Gauger, Paul G.; Miller, Barbra S.; Cohen, Mark; Hughes, David T.
Abstract : Purpose: The aim of this study was to determine clinical outcomes in patients with differentiated thyroid cancer after surgery and activity-adjusted 131 I therapy informed by diagnostic 131 I scans with SPECT/CT (Dx scan). Methods: Single-institution retrospective cohort study analysis of clinical outcomes after 1 to 5 years (mean, 39.6 ± 23.4 months) of follow-up in 350 patients with differentiated thyroid cancer associated with histopathologic risk factors, nodal metastases, and/or distant metastases. Postoperatively, all patients underwent Dx scans for completion of staging and risk stratification, and 131 I therapy was based on integration of information from histopathology, stimulated thyroglobulin and scintigraphy. Results: Twenty-three patients (6.6%) underwent reoperative neck dissection for removal of unsuspected residual nodal metastases identified on Dx scans. Clinical outcomes were as follows: 84.3% complete response, 1.4% biochemical incomplete response, 2.3% indeterminate response, and 12% structural incomplete response. Of the entire cohort, only 8 patients (2.3%) had persistent iodine-avid metastatic disease, which required repeated 131 I therapy. Of 31 patients with iodine-avid distant metastases identified on Dx scans, 13 patients (42%) achieved complete response with a single 131 I treatment. Conclusions: Detection of regional and distant metastases on postoperative Dx scans permits adjustment of prescribed 131 I activity for targeted treatment, as compared with fixed-activity ablation. This approach resulted in complete response after a single 131 I treatment in 88% patients with histopathologic risk factors and regional metastases and 42% patients with distant metastases. Most patients with structural incomplete response (81%) had elevated thyroglobulin levels with negative follow-up 131 I scans and positive PET/CT and/or CT scans consistent with altered tumor biology (non–iodine-avid disease). Abstract : Supplemental digital content is available in the text.